Construction for Fashion Design - Kiran Gobin; Anette Fischer (Great Britain Bloomsbury Visual Arts, 2017)
Construction is the foundation of fashion design; it takes passion and great skill to turn a two-dimensional drawing into a successful garment. Construction for Fashion Design guides readers through the process, teaching the theory, practical skills and techniques that they need to succeed. It leads readers through the essential stages of creating a garment, from pattern cutting and draping on the mannequin to sewing techniques and haberdashery. This fully revised and expanded second edition features insightful case studies with leading creative practitioners at the cutting edge of the fashion industry today, complete with detailed, step-by-step exercises that enable readers to contextualise their knowledge and put it into practise for the creation of their own successful projects.
Age Group: Adult
Keywords: Fashion; Design; (FSD111) Introduction to Fashion Product (Workshop)